PHRASEOLOGICAL EQUIVALENCE IN ENGLISH AND UZBEK LANGUAGES (American Journal of Pedagogical and Educational Research, 2026)
This article provides a comprehensive comparative-typological analysis of phraseological equivalence between English and Uzbek. Within the framework of the modern anthropocentric paradigm, phraseological units (PUs) are examined as linguistic mirrors reflecting national mentalities and cultural values. The study categorizes a targeted corpus of 20 idiomatic expressions into three hierarchical levels: full, partial, and zero equivalence. By analyzing contextual examples extracted from authentic English and Uzbek literary sources, the research explores how universal human logic and specific national realia shape the linguistic picture of the world.